Eksplorasi Keseimbangan: Analisis Kritis Buku Teks Bahasa Inggris sebagai Konten Lokal di SDN 04 Maiwa Enrekang - Suhria, Suhria; Irmayanti; Natsir, Indrawati; Rasyid, Asriadi (STKIP Paris Barantai, 2026)
This study aims to analyze whether English textbooks at SDN 04 Maiwa Enrekang as local content accommodate local content and contain contextual or authentic material. The method used is qualitative content analysis with a directed approach to the book